Urgensi Partisipasi Masyarakat Dalam Pembentukan Produk Hukum Daerah - Fathol Bari; Heriyanto Heriyanto (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
It is hoped that the formation of regional regulations can be a solution in forming aspirational legal products in the region by involving community components. In addition, through the preparation of a program for the formation of regional regulations regarding the Program for the Formation of Regional Regulations which involves the community as definite, standard, standard, systematic and planned guidelines, it is possible to create aspirational regional legal products that can be accepted and implemented among the community. By involving the community in the formation of regional legal products, it will have a positive impact in creating a peaceful, orderly and prosperous society in the context of regional autonomy. Based on this, the problem identification that can be formulated is how the community plays a role in the formation of regional legal products. So that it can create regional legal products that are aspirational and in line with community development.